MENGUKUR DETERMINAN KINERJA USAHA KEDAI KOPI DI PANTAI INDAH KAPUK (PIK) JAKARTA DI MASA AWAL PANDEMI COVID-19 - Santoso, Greffin Geraldy; Christian, Michael (Jurnal Pengabdian dan Kewirausahaan, 2021)
The development of the Food & Beverages (F&B) sector which encourages changes in the lifestyle of the people in Indonesia has contributed to the attractiveness of business in this sector. One of the interesting businesses in this sector is a coffee shop. The growth of this coffee shop business indirectly contributes to the national economy. Coffee consumption in Indonesia can also directly shape the pattern or lifestyle of consuming a variety of coffee, one of which is the style of consuming coffee in a coffee shop. This has also shaped the increase in the number of coffee shops in Indonesia. From an entrepreneurial perspective, this phenomenon is an opportunity that can be exploited. However, not all coffee shop entrepreneurs see this situation. With the existing phenomena, this study aims to analyze the performance of the coffee shop business using exogenous variables, namely market orientation, entrepreneurial orientation, and innovation. This research is a quantitative research using regression analysis using SPSS. The sample in this study was 75 coffee shop entrepreneurs in Pantai Indah Kapuk (PIK), Jakarta. The results of this study explain that all hypotheses are accepted. Market orientation in this case affects business performance. Likewise with the entrepreneurial orientation that affects business performance. Furthermore, innovation also affects business performance of coffee shops in this region. Simultaneously, each exogenous variable affects business performance at PIK. The overall results of this study are also still relevant and in line with several previous studies. From these results it can be explained that making strategies and making decisions that affect business performance. In addition, pay attention to competitors' strategies by understanding competitors' strengths and weaknesses. For further researchers, other additional variables that are not included in this study in determining business performance, such as the financial ability of businesses to survive or compete.